Digital Storytelling for Employability - Malita, Laura; Boffo, Vanna (Proceedings e report, 2010)
This publication results from the research work undertaken by the partner institutions involved in the KA3-ICT Project Transversal Lifelong Learning Programme, Learn about finding jobs from digital storytelling(143429-2008-LLP-RO-KA3-KA3MP), with the main purpose of enhancing graduates' employability possibilities. For graduating students looking for a job it is perhaps harder than ever to meet success on the job market. They must use every tool they know to express themselves and to reflect their knowledge, competences and skills. The book aims to explain the main aspects of using digital storytelling as a method for employability, career development, reflection, assessment, consultancy, presentation and communication. Through digital storytelling, students begin to comprehend how all the elements of writing a narrative work together and how to manipulate them for the best effects in readers and viewers. Also, sharing and evaluating digital stories among peers is an excellent way to foster self-expression and tolerance and to create an engaged community of learners.